Social and Legal Implications of Contractual Marriage on Child Support Responsibility - Rizky Pratama; Lestari Anindya (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2020)
The phenomenon of contract marriage (temporary marriage) in Indonesia often causes social stigma and legal uncertainty, especially regarding the rights of children born from these relationships. This research explores the social and legal implications of contract marriage on fulfilling child support obligations and proposes legal solutions to protect children's rights. Using a juridical-sociological approach and empirical legal methods, the research results show that children often face discrimination due to unregistered marriages and difficulty obtaining birth certificates or claiming support. Strengthening marriage registration regulations, retrospective registration through marriage certificates, as well as comprehensive child protection services are essential to ensure these children receive proper recognition and support.